Community use of masks as a preventive measure for Covid-19 in Kabale district of Uganda - Ssaka, Mustafa; Lwanga, Charles; Eren, Tunc; Alimoglu, Orhan (International Journal of Human and Health Sciences (IJHHS), 2020)
Coronavirus disease 2019 (Covid-19) caused a global pandemic and by June 1st, 2020, the global numbers of Covid-19 cases reached six million with more than 370,000 deaths. Community-wide mask wearing may contribute to the control of Covid-19 by reducing the amount of emission of infected saliva and respiratory droplets from persons with subclinical or mild Covid-19. However, use of masks in public and in health care facilities has been controversial as different organizations and agencies established different guidelines. In Uganda, not any reports on mask utilization practices have been published yet. Therefore, this report aims at documenting mask use practices, as observed in our interactions with non-Covid-19 patients and their relatives at Kabale regional referral hospital as well as Kabale town residents. It was observed that many non-Covid-19 patients and the relatives of hospitalized patients only wear their masks on reaching the hospital premises while community members of Kabale town wear their masks only in the presence of security agencies and individuals in the public only wear masks in places where they would be refused from services without masks. Wearing of masks in public places and health care facilities together with other preventive measures including hand hygiene, social distancing and wearing of full personal protective equipment for health care providers working on Covid-19 patients are key measures in preventing the spread of infection. There is an increased need for intensified community educational activities on public awareness of the importance of appropriate use of masks. International Journal of Human and Health Sciences Vol. 05 No. 02 April’21 Page: 267-270